Legal Analysis of the Prosecutor's Office Performance in Handling Mega Corruption Cases in Indonesia: Analisis Hukum Terhadap Kinerja Kejaksaan dalam Menangani Kasus-Kasus Mega Korupsi di Indonesia - Rajagukguk, Meryana; Djoyosugito, M. Alirahman (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
The handling of mega corruption cases such as BLBI, Jiwasraya, and Asabri serves as a key indicator in measuring the effectiveness of the Attorney General's Office as a law enforcement institution. This study aims to analyze the role and performance of the Attorney General's Office in dealing with large-scale corruption cases and to identify the inhibiting factors that affect it. The research method used is normative juridical with a literature study approach, focusing on statutory regulations, court decisions, as well as relevant literature and scientific journals. The results show that although the Attorney General's Office possesses a strong legal basis and authority, various obstacles remain, such as limited human resources, weak inter-institutional coordination, and external pressures. The conclusion of this study indicates that the effectiveness of the Attorney General's Office in eradicating mega corruption requires institutional strengthening, system improvement, and increased integrity and professionalism among law enforcement officers.